Serah jajah dan perlawanan yang tersisa : etnografi orang rimba di Jambi - Adi Prasetijo (Jagakarsa, Jakarta : Wedatama Widya Sastra, 2011)
On social life and customs of Kubu people in Jambi Province, Indonesia.
Includes bibliographical references (p. 295-308).
Keywords: Kubu (Indonesian people) -- Social life and customs; Jambi (Indonesia : Province) -- Social life and customs